Figuring And Disfiguring: Audience Participation In Qur’anic Exegesis on Instagram - Rusydiana, Naili Rosa Urbah; Rosyada, Melynia; Sholiha, Marwa Mar’atus; Mohammad Afri Muadom (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2025)
This study examines how audience participation on Instagram shapes the dynamics of digital interpretation, particularly through the processes of figuring (affirming meaning) and disfiguring (reinterpretation or critique) in comments on Quranic verse posts. The research is motivated by the shifting paradigm of religious authority in the social media era, where interpretation is no longer monopolized by authoritative figures but openly negotiated and contested by users. The study focuses on two public accounts: @ismaelalkholilie, representing a sufistic-affective style, and @nadirsyahhosen, reflecting a contextual-critical approach. Using a descriptive qualitative method and digital hermeneutics, data were collected through online observation, caption documentation, and analysis of comments on two posts (January–May 2025). Findings show that audiences are active co-interpreters rather than passive recipients. Comments on Ismael’s account are mainly affective and affirm spiritual narratives, while those on Nadirsyah’s account are more reflective, intellectual, and critical. Digital interpretation thus emerges as dialogical, decentralized, and shaped by audience participation.